Azo-dye Orange II degradation by Fenton's reaction using Fe/ZSM-5 zeolite as catalyst - Filipa Duarte (2009)
This work deals with the non-biodegradable azo-dye Orange II degradation using the heterogeneous Fenton-like reaction using Fe/ZSM-5 zeolite as catalyst. The influence of some relevant parameters was studied, namely pH and temperature in the ranges 3.0 8.5 and 30 53 ºC, respectively. Decolorization degree, TOC removal and leaching were evaluated along time in the experiments done. It was found that temperature has a predominant effect in OII concentration and TOC reduction while pH is more important in the metal loss from the support. Degradation increases with temperature and leaching decreases when initial pH value increases. It was possible to decolorized OII under less acidic conditions than those conventionally performed in Fentons oxidation, compensating this with the increase of temperature (30 to 35 ºC for a pH increase from 3.0 to 5.2), which is a promising approach since textile effluents are characterized by high temperatures and pH values.